Antioxidative Potential of the Polyphenolics of Stephania japonica var. Discolor (Blume) Forman: A Chromatographic (High-Performance Liquid Chromatography) and Spectrophotometric Measure. Issue 4 (2nd April 2016) - Uddin, Md. Nazim; Ahmed, Nazim Uddin; Rahman, Md. Atiar; Akter, Rasheda; Akter, Rehana
Abstract : This study investigated the quantitative phytochemical contents, total phenolics, total flavonoids, total carotenoids, antioxidative capacity, tannin, proanthocyanidins, lycopene, chlorophyll a, and chlorophyll b of the Stephania japonica extract. Comprehensive antioxidative effects of the extract were also investigated. Quantitative assays were conducted through both spectrophotometric and high-performance liquid chromatographic methods. Antioxidative effects were measured through FeCl3 reducing power, metal chelating power, reducing power, 2, 2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid (ABTS) scavenging activity, N, N-dimethyl-1, 4-diaminobenzene free radical scavenging activity, superoxide radical scavenging activity, and nitric oxide scavenging effect. The contents of total phenolics, total flavonoids, total carotenoids, total antioxidative capacity, tannin, proanthocyanidins, lycopene, chlorophyll a, and chlorophyll b were found to be 47.32 ± 0.75 mg tannic acid equivalent, 61.41 ± 1.58 mg catechin equivalent, 63.29 ± 2.21 mg, 22.85 ± 0.70 mg ascorbic acid equivalent, 76.17 ± 0.97 mg tannic acid equivalent, 94.96 ± 4.49 mg catechin equivalent, 22.19 ± 0.79 µg, 22.19 ± 0.79 µg, 7.52 ± 1.24 mg, and 10.43 ± 2.11 mg, respectively, in 1 g of ethanol extract. A high concentration of epicatechin, p -coumaric acid, and rutin hydrate and moderate concentration of caffeic acid and quercetin was detected in the extract. The IC50 value for ferric reducing power assay, metal chelating assay, reducing power assay, ABTS scavenging assay, N, N-dimethyl-1, 4-diaminobenzene scavenging assay, superoxide scavenging assay and nitric oxide (NO) assay were 465.06 ± 7.32 µmol ascorbic acid/g, 1656.52, 270.55, 457.27, 632.74, 217.5, and 464.00 µg/mL, respectively. No beta carotene was detected in the extract. The extract was demonstrated to be a very potential source of antioxidative metabolites.